Silicon-enriched hydroxyapatite formed induced by REFIX-based toothpaste on the enamel surface - Vilhena, Fabiano Vieira; Lonni, Audrey Alesandra Singhen Garcia; D'Alpino, Paulo (Brazilian Dental Science, 2021)
Objective: This in vitro study aimed at characterizing the mineral content and filler particle morphology of a fluoridated toothpaste containing REFIX technology and the mineral content and the morphology of the enamel surface treated with this product. Material and Methods: Bovine enamel blocks (n=5) were obtained (4×4×6 mm), demineralized (artificial caries lesion), and treated (pH cycling and brushing with the toothpaste). During the pH cycling, which lasted for 7 days (demineralization and remineralization took 6 h and 18 h, respectively), the enamel was brushed for 5 min using an electric toothbrush before being immersed in a remineralization solution. We evaluated the micromorphology and elemental levels (wt%) of ions present in the toothpaste and on the layer formed over the enamel following the treatment. The surface morphology was assessed using scanning electron microscopy (SEM). The elemental analyses were performed using an energy-dispersive X-ray spectrometer (EDS). Results: Scanning electron micrographs of the toothpaste demonstrated a uniform size distribution of regular-shaped fillers sparsely organized in nanoclusters. Elemental analysis of the toothpaste’s formulation demonstrated the presence of Si (silicon), Na (sodium), P (phosphorus), and F (fluorine), among others. We also detected a mineral layer that had formed on the treated enamel surface; the layer had a consistent uniform thickness of 14 µm. Conclusion: Based on the results, it can be stated that REFIX technology modifies the surface and subsurface of the enamel structure, forming a Si-rich mineral layer. KEYWORDS Dental enamel; Dentifrice; Scanning electron microscopy; Tooth remineralization.